PROFIL PEMECAHAN MASALAH SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL SISWA KELAS VIII SMPN 21 PALU DITINJAU DARI KEMAMPUAN MATEMATIKA - Nur Padila Susanti; Ibnu Hadjar; Pathuddin Pathuddin (Universitas Tadulako, 2025)
This study aims to obtain a problem-solving profile of a two-variable linear equation system for grade VIII students of SMP Negeri 21 Palu reviewed from the student’s mathematical abilities based on Polya steps. This study uses a qualitative method with a qualitative descriptive approach based on the problem-solving steps proposed by Polya. The results of the study showed that the subjects used in this study were three students, namely students with high mathematical ability (ZN), students with moderate mathematical ability (LT), and students with low mathematical ability (KB). The results of the study showed that subjects who had high, medium and low mathematical abilities in solving SPLDV mathematical problems were as follows: (1) in understanding problems, subjects with high mathematical abilities and were reading problems repeatedly, as well as their knowledge of